Effects of In ovo Injection of Stimulant Solutions on Growth and Yolk Utilization in Broiler Embryos - McGruder, B.M.; Zhai, W.; Keralapurath, M.M.; Gerard, P.D.; Peebles , E.D. (International Journal of Poultry Science, 2011)
Effects of the automated in ovo injection of stimulant solutions (200 μL) on growth and yolk utilization in the broiler embryo was investigated in 3 trials. Treatment solutions were injected into the amnion of embryos on d 16 of incubation. Treatment effects on 0 to 18 d percentage incubational egg weight loss, proportional embryo BW, proportional yolk sac weight and embryo and yolk sac moisture contents on d 18 were determined. In trial 1, 1 mM caffeine decreased proportional embryo BW and increased percentage embryo mortality and moisture content. At 1 x 10-3 and 10-6 mM concentrations, caffeine decreased proportional embryo BW and at a 1 x 10-6 mM concentration, caffeine increased percentage embryo moisture concentration. However, caffeine at concentrations of 1 x 10-3, 10-6 and 10-9 mM had no detrimental effect on embryo survivability. Theophylline, creatine, or phosphocreatine at a 1 mM concentration in trial 2 and theophylline, creatine, or L-arginine at a 1 mM concentration in combination with 5.5 mM potassium chloride in trial 3 did not affect any of the parameters examined. The current study indicated that except for 1 mM caffeine, the tested stimulant solutions had no detrimental effects on embryogenesis, suggesting their potential use as stimulants in the commercial injection of broiler hatching eggs. However, they may have to be used at different concentrations or at different times of incubation than those used in this study in order to improve embryo growth and yolk nutrient utilization, while having no detrimental effect on embryo survivability.